METAFORA KONSEPTUAL DALAM RUBRIK TEKNOLOGI KORAN ELEKTRONIK KOMPAS - Fathiyyah Sekar Widiasri; Tajudin Nur (Universitas Muhammadiyah Surakarta, 2020)
This article employs a cognitive semantic analysis with the aim to describe the types of metaphors and conceptual meanings based on conceptual metaphor theory by Lakoff and Johnson (1980), and image schemes based on image scheme theory by Cruse and Croft (2004) on the electronic newspaper Kompas. Data source in this research are taken from the technology rubric of the electronic newspaper Kompas on the March 2020 edition. We use descriptive qualitative method to conduct the reseach. The result shows that there are 16 data found of conceptual metaphor, there are nine data of structural metaphor with the conceptual meaning of enemy, leader, and human; four data of orientational metaphor with the concept of meaning of space and quality, and three data of ontological metaphor with the concept of meaning of money and fame. For the image scheme, there are four types that are found, 5 data of force scheme, 6 data of existence scheme, 1 data of container scheme, and 4 data of space scheme. Keywords: Conceptual metaphor, cognitive semantic, technology rubric of Kompas.com